Critical multifunctional role of the betaine aldehyde dehydrogenase gene in plants. Issue 4 (4th July 2018) - Golestan Hashemi, Farahnaz Sadat; Ismail, Mohd Razi; Rafii, Mohd Y.; Aslani, Farzad; Miah, Gous; Muharam, Farah Melissa
ABSTRACT: The betaine aldehyde dehydrogenase ( BADH ) gene plays a multifunctional role in plants. It is an important factor in fragrance production, abiotic stresses and antibiotic-free selection of transgenic plants. Molecular studies have presented a new picture of this critical factor involved in abiotic stress responses via the MAPK (mitogen-activated protein kinase) signalling pathway in numerous plants. Besides BADH, glycine betaine performs an important function in plant tolerance to environmental stresses. The presence of glycine betaine can help maintain the integrity of cell membranes against unexpected environmental stresses. BADH leads to production of glycine betaine through the oxidation of betaine aldehyde. Hence, BADH is considered a key regulator for glycine betaine formation. Consequently, by providing glycine betaine as a chemical interface, there is a critical role of BADH in enhancing the tolerance in an extensive range of plants subjected to different destructive abiotic stresses. The present article reviews the significant multifunctional role of the BADH gene in various plants, and also particularly argues how this important gene plays a responsive function to different destructive abiotic stresses, and its potential use in crop improvement using advanced technologies. Consequently, cloning of more BADH genes, specially from stress-tolerant plants, discovering their responsive signalling roles under environmental stresses, and validating such candidates for their potential are very helpful, and can open new windows to generate new stress-resistant crop cultivars.